Integrating Telecollaboration for Intercultural Language Acquisition at Secondary Education: Lessons Learned - Jauregi Ondarra, M.K. (Research Publishing Net, 2015)
The TILA project originated from the need to explore whether and how telecollaboration affects language learning processes for communication, intercultural understanding and motivation of youngsters learning foreign languages at secondary schools and to empower teachers to pioneer meaningful pedagogical innovation in the curriculum of foreign languages at secondary schools. In the 2,5 year lasting project 837 pupils, 300 student teachers and 48 teachers participated in telecollaboration exchanges. The results show that task-based telecollaboration can be successfully integrated in the foreign language curriculum by blending different pedagogical activities. These exchanges can contribute to enhance pupils’ communicative competence, intercultural awareness and motivation.
Keywords: call, telecollaboration, intercultural competence, motivation; multimodal interaction; teacher training; tasks